1993
DOI: 10.3354/meps097287
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of phytoplankton primary productivity in the Neuse River estuary, North Carolina, USA

Abstract: Phytoplankton primary productivity in the Neuse Rlver estuary (North Carolina. USA) was assessed for spatial and temporal patterns over 4 yr as a function of associated influential factors, especially biomass (chlorophyll a, chl a) and light. From I4CO2-uptake assays maximum photosynthetic rates (P,,,,,), photosynthesis versus irradiance relationships, daily pnmary productivity (Pd), and annual pnmary productivity (P,) for the system were calculated. Both physical and chemical characteristics of the estuary we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 17 publications
5
44
1
1
Order By: Relevance
“…The inability to demonstrate different responses for the NO3-and the NO3-+ POd3 treatments suggested that P was not limiting for phytoplankton growth. These results support previous nutnent bioassay and uptake kinetics results for Neuse River Estuary phyioplankton conducted during the past decade (Paerl 1987, Stanley 1988, Rudek et al 1991, Boyer et al 1993, 1994. The duration of the mesocosm bioassay incubations (6 d) was sufficient to allow at least a 3-fold increase in phytoplankton biomass.…”
Section: Discussionsupporting
confidence: 78%
“…The inability to demonstrate different responses for the NO3-and the NO3-+ POd3 treatments suggested that P was not limiting for phytoplankton growth. These results support previous nutnent bioassay and uptake kinetics results for Neuse River Estuary phyioplankton conducted during the past decade (Paerl 1987, Stanley 1988, Rudek et al 1991, Boyer et al 1993, 1994. The duration of the mesocosm bioassay incubations (6 d) was sufficient to allow at least a 3-fold increase in phytoplankton biomass.…”
Section: Discussionsupporting
confidence: 78%
“…It has been indicated that variations in river flow, governed primarily by watershed rainfall, regulate the magnitude of estuarine primary production and periodicity of algal blooms, influence a seasonal shift in limiting nutrients and affect the extent of seasonal oxygen depletion in summer (Malone et al 1988, Dortch & Whitledge 1992, Fisher et al 1992, Boyer et al 1993, Mallin et al 1993. The impact of freshwater input on phytoplankton dynamics is likely to vary among systems, although functional similarities may be expected.…”
Section: Discussionmentioning
confidence: 99%
“…l . Because of highly colored and turbid waters, primary productivity in this estuary is dominated (>g0 %) by planktonic (as opposed to benthic) phototrophs (Boyer et al 1993, Paerl et al 1995. The OM loading attributable to planktonic productivity was calculated by multiplying primary productivity and water volume (m3) for 6 representative segments of the estuary and integrating the value over the length of the study area.…”
Section: Methodsmentioning
confidence: 99%